Waltzing the blues away - Rose, Billy, 1899-1966.; Macdonald, Ballard; State Theatre (Sydney, N.S.W.); David, Lee, 1891-1978 (1900)
Part of the State Theatre collection of cinema scores and parts, mainly used for silent movies, but including musical materials associated with talking pictures ca. 1900-1950, used by the State Theatre and various film distribution companies throughout Australia. Some items include performance annotations.
Keywords: Dramatic music; Instrumental music -- Scores and parts; Silent film music